Show that $$1+(x_1x_2...x_n)^{\frac{1}{n}} \leq [(1+x_1)(1+x_2)...(1+x_n)]^{\frac{1}{n}}, \forall x_i \geq 0, \ i = 1,2,3...,n$$

So, I have to make this function something like this:

$$f(t_1x_1+t_2x_2+...t_nx_n) \leq t_1f(x_1)+t_2f(x_2)...+t_nf(x_n)$$ Also, I need to choose an $f(x)$ such that the inequality holds and $f''(x) > 0$ to show that this is a convex.

Ok, so it is getting really difficult for me as I don't understand what to choose as $t_i$ and what to choose as $f(x)$. All I can do is this:

$$1+[e^{\log(x_1x_2...x_3)^{\frac{1}{n}}}] \leq e^{\log[(1+x_1)(1+x_2)...(1+x_n)]^{\frac{1}{n}}}$$

Maybe I can choose $f(x) = \log(x)$, but that'd give me $f''(x) < 0.$ Can anyone please help me figure out what $t_i$ and $f(x)$ should be in order to make it a convex? Thanks.

  • $\begingroup$ Maybe you could use induction on $n$ and then just have to prove the case for $n=2$. $\endgroup$ – bgins Jul 24 '15 at 17:55
  • $\begingroup$ @bgins, I think I could. But, I am trying to learn it in the way as above. $\endgroup$ – Jellyfish Jul 24 '15 at 18:01
  • $\begingroup$ Maybe try $f(x)=\log(1+x)$, $t_i=1$ and deal with $f$ being concave in stead of convex (so $-f$ would be convex). $\endgroup$ – bgins Jul 24 '15 at 18:12
  • $\begingroup$ Related: math.stackexchange.com/questions/29357/… $\endgroup$ – user940 Jul 24 '15 at 21:00

You may take $g(t)=\log(1+e^t)$. We have: $$ g''(t) = \frac{e^t}{(1+e^t)^2} $$ hence $g$ is a convex function. Let $x_i=e^{t_i}$. Jensen's inequality hence gives:

$$ \log\left(1+\exp\left(\frac{t_1+\ldots+t_n}{n}\right)\right)\leq \frac{1}{n}\sum_{i=1}^{n}\log(1+e^{t_i})$$ and by exponentiating the previous line: $$ 1+\left(x_1\cdot\ldots\cdot x_n\right)^{\frac{1}{n}}\leq\left((1+x_1)\cdot\ldots\cdot(1+x_n)\right)^{\frac{1}{n}}$$ i.e. the super-additivity of the geometric mean, follows.


You can invoke Maclaurin's Inequality (https://en.wikipedia.org/wiki/Maclaurin%27s_inequality). Let $S_k$ be the average symmetric sum of degree $k$ for $x_1,x_2,\ldots,x_n$ and $k=0,1,2,\ldots,n$. Then, $\sqrt[k]{S_k}\geq \sqrt[n]{S_n}$ for every $k$. Note also that $1=S_0=S_1^0$ (where we take $0^0$ to be $1$), and $S_1\geq\sqrt[k]{S_k}$ for all positive $k$. Now, since $\prod_{i=0}^n\,\left(1+x_i\right)=\sum_{k=0}^n\,\binom{n}{k}\,S_k$, we get $$\prod_{i=0}^n\,\left(1+x_i\right) \geq \sum_{k=0}^n\,\binom{n}{k}\,\left(\sqrt[n]{S_n}\right)^k=\left(1+\sqrt[n]{S_n}\right)^n\,.$$ Also, you can show that $$\prod_{i=0}^n\,\left(1+x_i\right) \leq \sum_{k=0}^n\,\binom{n}{k}\,S_1^k=\left(1+S_1\right)^n\,.$$ Hence, $$1+\sqrt[n]{\prod_{i=1}^n\,x_i}\leq\sqrt[n]{\prod_{i=1}^n\,\left(1+x_i\right)}\leq 1+\frac{\sum_{i=1}^n\,x_i}{n}\,.$$ However, you can also achieve the inequalities above by applying AM-GM too.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.